2014
DOI: 10.4081/ijas.2014.3104
|View full text |Cite
|
Sign up to set email alerts
|

In VitroActivity ofPithecellobium DulceandLysiloma Acapulcensison Exogenous Development Stages of Sheep Gastrointestinal Strongyles

Abstract: An experiment was conducted to evaluate the effects of two lyophilised aqueous extracts of Lysiloma acapulcensis (LAE) and Phitecellobium dulce (PDE) tree leaves on in vitro assessment of hatching of eggs, larval development and migration of gastrointestinal nematodes of sheep using a general linear model. Treatments contained extracts from both species at concentrations of 0, 125, 250 and 500 µg/mL. Both albendazole and levamisole were used at a level of 1% as positive control. The extract of LAE, compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
7
1
1
Order By: Relevance
“…G. sepium also showed the greatest EHI effect, followed by P. dulce and L. leucocephala . The results obtained for G. sepium generally indicated more potent effects than reported in previous studies [ 42 , 43 , 48 ], unlike the results obtained for P. dulce [ 46 ] and L. leucocephala [ 49 ]. The effects on the ME and LE percentages were greatest for G. sepium , as demonstrated by the effect of its extract, which inhibited H. contortus embryonic development and egg hatching.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…G. sepium also showed the greatest EHI effect, followed by P. dulce and L. leucocephala . The results obtained for G. sepium generally indicated more potent effects than reported in previous studies [ 42 , 43 , 48 ], unlike the results obtained for P. dulce [ 46 ] and L. leucocephala [ 49 ]. The effects on the ME and LE percentages were greatest for G. sepium , as demonstrated by the effect of its extract, which inhibited H. contortus embryonic development and egg hatching.…”
Section: Discussioncontrasting
confidence: 72%
“…With respect to the three forage species focused on in this study, AA has been demonstrated against gastrointestinal nematodes such as H. contortus , Teladorsagia circumcincta , Trichostrongylus colubriformis , and Oesophagostomum columbianum . For example, G. sepium was shown to exert an anthelmintic effect in vitro against larvae [ 40 , 41 , 42 ] and eggs [ 42 , 43 ], while L. leucocephala affected larvae [ 44 , 45 ]; moreover, P. dulce inhibited larval development and migration [ 46 ] and reduced the elimination of eggs in goats in vivo [ 47 ]. Given the importance of these plant species as a food source in ruminants due to their nutritional and productive attributes, it is interesting to compare their anthelmintic effects in vitro as well as to identify the main compounds with potential effects on H. contortus .…”
Section: Introductionmentioning
confidence: 99%
“…Anthelmintic effects have been particularly found in the Caesalpinia genus. 23,24 These results coincide with those recorded in the present study, and could be related to the content of free condensed tannins, which is higher than in other leguminous species from the same region, such as Lysiloma acapulcensis 11 and Acacia cochliacantha. 4,8 Phenols, such as tannins, may negatively impact nematode egg hatching by binding to the egg cuticle which is rich in glycoproteins, forming a tannin-protein complex that may alter embryo development and eventually the hatching process.…”
Section: Egg Hatching Inhibitionsupporting
confidence: 91%
“…10 Lysiloma acapulcensis free condensed tannins (FCT) were used as internal standards. 11 Free condensed (FCT1), protein-bound (PCT) and fiber-bound (FCT2) tannins were identified following the technique reported by Porter et al 12 Purification was performed using a Shepadex LH-20 column, as described by Hedqvist et al 13…”
Section: Condensed Tannin Contentmentioning
confidence: 99%
“…Moreover, chemical treatments are costly when used regularly to prevent helminth parasites in livestock (Jabbar et al 2006). Consequently, there is an increasing interest in screening phytogenic extracts and medicinal plants as alternatives to the expensive traditional drugs (Olmedo-Juárez et al 2014;Cedillo et al 2015;Cervantes-Valencia et al 2015). It has been reported that medicinal plants not only possess anthelmintic activity, but also have antibacterial and insecticidal properties (Mejía-Hernández et al 2014).…”
Section: Introductionmentioning
confidence: 99%